2016
DOI: 10.1186/s13063-016-1161-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a behavioral incentive scheme linked to goal achievement: study protocol for a randomized controlled trial

Abstract: BackgroundChildhood obesity is a concern in Australia and across the world. Community-based weight management programs are an important response to address childhood obesity. However, the scientific literature suggests that their effectiveness could potentially be enhanced by providing a structured incentive scheme. This proposal aims to determine the effectiveness of enhanced goal setting linked to a structured incentive scheme designed to improve the sustained health and wellbeing of overweight/obese childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…A mixed-method qualitative study nested within a cluster randomized controlled trial (cRCT) was conducted in New South Wales, Australia, between 2014 and 2016 (Redfern et al, 2016). Qualitative research was conducted between the 6- and 18-month data collection points of the cRCT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed-method qualitative study nested within a cluster randomized controlled trial (cRCT) was conducted in New South Wales, Australia, between 2014 and 2016 (Redfern et al, 2016). Qualitative research was conducted between the 6- and 18-month data collection points of the cRCT.…”
Section: Methodsmentioning
confidence: 99%
“…Informed consent was obtained from all study participants, and the study was performed according to the Declaration of Helsinki. Full details of participant eligibility are detailed elsewhere (Redfern et al, 2016). Participants recruited for the qualitative research included two groups: "families" and "stakeholders."…”
Section: Participants Recruitment and Sampling Frameworkmentioning
confidence: 99%
“…Unfortunately, the original version of this article [ 1 ] contained an error. An author’s name was spelt incorrectly.…”
mentioning
confidence: 99%
“…227 It has been suggested that a population-wide weight loss was associated with a marked reduction in CVD mortality in Cuba. 228 A few community-based weight loss programs have initiated in Australia; 229,230 however, there is no national-level strategies or programs to manage the weight loss. The intervention of increased physical activity and reduced sedentary time could substantially lower the CVD burden.…”
Section: Implications Of the Findingsmentioning
confidence: 99%